Pengaruh Pengangguran Terhadap Pertumbuhan Ekonomi (IJM: Journal of Multidisiplinary, 2024)
The aim of this study is to find out the impact of unemployment in Indonesia on the growth of the country's economy. Where Indonesia is one of the developing countries whose economy needs more attention. There are many factors causing the progress of a country's economy, one of which is the level of public income. Indonesia is experiencing a decline over the unemployment rate, but some 43 million people are still unemployed. This must be overcome by the government, in order to create the well-being of the Indonesian people, which of course also influences the growth of the country's economy. Analysis of the impact of unemployment on the growth of the country, carried out through the method of study of libraries from relevant sources, both government data and previous research. Based on the study of the library obtained that generally unemployed has an influence on economic growth in Indonesia in terms of public income, social costs, capital investment as well as the income of the state. The government's strategy for unemployment is to develop labour productivity, expand employment opportunities and develop human resources (HRM) in support of employment.